On some taxonomically confused species of the genus Amphiesma Duméril, Bibron & Duméril, 1854 related to Amphiesma khasiense (Boulenger, 1890) (Squamata, Natricidae) - David, Patrick; Vogel, Gernot; Rooijen, Johan Van (Zootaxa, 2013)
Three species of the genus Amphiesma Duméril, Bibron & Duméril, 1854 have long been confused in the literature, with each other and with other species of the genus. Amphiesma khasiense (Boulenger, 1890) has been considered to inhabit a large geographical region, extending from north-eastern India, east to Vietnam and southern Thailand. Amphiesma boulengeri (Gressitt, 1937) has been regarded as a species endemic to south-eastern China. Amphiesma inas (Laidlaw, 1901) has been recorded from West Malaysia, Thailand and Indonesia (Sumatra). A multivariate analysis of morphometric and meristic characters shows that these three species can be separated by combinations of characters in the scalation and pattern, the most obvious being the structure of the postocular streak. On the basis of our analysis and after comparison with name-bearing type specimens, Amphiesma khasiense is restricted to north-eastern India, Myanmar, western Yunnan Province of China, northern Laos and northern and western Thailand. Other populations from south-eastern China, Vietnam, other parts of Laos, Cambodia and central Thailand, which have been recorded in the literature as A. khasiense, A. johannis or Amphiesma modestum (Günther, 1875), should be referred to Amphiesma boulengeri. Amphiesma inas (Laidlaw, 1901) is a valid species endemic to mountain ranges of southern Peninsular Thailand and West Malaysia. The mention of Amphiesma inas in Sumatra is erroneous, being based on the second known specimen of Amphiesma kerinciense David & Das, 2003, which is here redescribed. A key to species of the Amphiesma khasiense group and other species sharing a greyish-brown background without conspicuous dark and pale stripes, is provided.